Optimalisasi Pembelajaran Melalui Teknologi Pendidikan dalam Implementasi Kurikulum Merdeka di Indonesia - Andriansah Andriansah (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
The development of educational technology has significantly impacted the implementation of the Merdeka Curriculum in Indonesia. This study aims to explore how educational technology can optimize learning in accordance with the principles of the Merdeka Curriculum. The method used is literature analysis, involving a review of various sources on educational technology and the curriculum. Findings indicate that the utilization of technology, such as digital learning platforms and collaborative tools, can enhance interactivity, accessibility, and student engagement. The implications of this research emphasize the importance of integrating technology into the curriculum to create learning experiences that are more relevant and responsive to student needs. Thus, educational technology can be key to achieving more effective educational goals in the digital era.